Comparative metagenomics of wild and cultivated Fragaria chiloensis reveals major rhizosphere microbiome shifts linked to stress adaptation - Carlos Farkas; Matías Guerra; Adan Andreu Heredia; Jean Franco Castro (Current Research in Microbial Sciences)
Fragaria chiloensis ssp. chiloensis, endemic to Chile, includes a wild form (f. patagonica) and a cultivated “white strawberry” (f. chiloensis) historically grown in central-south Chile. In this study high throughput metagenomic sequencing was employed to examine the rhizosphere microbial communities of wild and cultivated plants were examined to explore how domestication has shaped microbial structure and function. This enabled binning and functional annotations indicating that wild rhizospheres were dominated by Frankia and Bradyrhizobium, whereas cultivated samples exhibited broader genus‐level diversity yet preserving a core ecological function through functional redundancy. Metabolic reconstructions further spotlight high‐biomass taxa, with Frankia in wild plants and Nocardia in cultivated plants, that harbored extensive biosynthetic gene clusters, linking robust growth to specialized metabolite production and putative osmoprotection. Collectively, these findings illustrated how domestication reshapes the rhizosphere microbiome and contributes to One Health-aligned strategies for sustainable agriculture.